Analyzing urban damage and surface deformation based hazard-risk in Kathmandu city occurred during Nepal earthquake (2015) using SAR interferometry. Issue 12 (15th December 2022) - Kumar, Amit; Manisha,; Lal, Preet; Prasad, Alisha; Tripathy, Pratyush; Saikia, Purabi
Abstract: The study focuses on urban damage and surface deformation in the Kathmandu city region that occurred due to the massive earthquake in Nepal in 2015. The deformation was estimated from pre-and post-earthquake C-band Sentinel-1A synthetic aperture radar (SAR) satellite images employing the Interferometric SAR (InSAR) technique. The study highlighted a latitudinal pattern in deformation from the north to south directions, most likely directed by the structural alignments (ridges and valleys) in the Himalayan region. The city-scale study exhibited an increase in the intensity of displacement from the north (<-5cm) to the south (>-20 cm) direction in Kathmandu city. Major parts of the city observed moderate subsidence (-10 cm to −15 cm), while the south-eastern and central parts observed severe subsidence (>15 cm) due to structural damage and collapse of buildings. The incidences of land subsidence and damage to buildings were recorded in the entire Kathmandu Municipal Corporation (KMC) area - a large part (86%; 43.84 km 2 ) of which was built-up land and inhabited population (49% of 1, 744, 240 people) in 2015 - affecting built structures, transport networks, and world heritage monuments. The earthquake hazard-risk analysis demonstrated that the built-up land in the south-eastern and north-western parts were the severely affected areas due to high population and high built-up density. The study elucidates the potential application of InSAR technology using freely available concurrent Sentinel-1A SAR data in the estimation of earthquake induced damage study at urban scale and hazard-risk assessment that aid in the formulation of an effective disaster risk reduction policy framework for the region.